Interaction Effect Between Copy Number Variation in Salivary Amylase Locus (AMY1) and Starch Intake on Glucose Homeostasis in the Malmö Diet and Cancer Cohort - Hamid, Aida Koder; Andersson-Assarsson, Johanna; Ericson, Ulrika; Sonestedt, Emily (Frontiers in Nutrition, 2021)
Salivary amylase initiates the digestion of starch and it has been hypothesized that salivary amylase may play a role in the development of insulin resistance and type 2 diabetes. The aim was to examine the interaction between copy number variation in the salivary amylase gene AMY1 and starch intake. We studied 3,624 adults without diabetes or elevated blood glucose in the Malmö Diet Cancer cohort. We assessed the associations and interactions between starch intake, AMY1 copies and glucose homeostasis traits (i.e., fasting plasma glucose, insulin and HOMA-IR) and risk of type 2 diabetes over an average of 19 follow-up years. AMY1 copy number was not associated with glucose, insulin or HOMA-IR. We observed a significant interaction between starch intake and AMY1 copies on insulin and HOMA-IR after adjusting for potential confounders (p<0.05). The inverse association between starch intake and insulin and HOMA-IR was stronger in the group with 10 or more copies (Ptrend<0.001). In addition, we observed an inverse association between starch intake and type 2 diabetes in the group with 10 or more copies (ptrend=0.003), but not in the other groups. This cross-sectional observational study suggests that AMY1 copy numbers might interact with starch intake on glucose homeostasis traits. Interventional studies are required to determine whether individuals with high AMY1 copy numbers may benefit from a high starch intake.